Kebertahanan Seni Kerajinan Anyaman Bambu Di Desa Tri Rukun Kabupaten Boalemo Provinsi Gorontalo - I Wayan Sudana; Sang Putu Sumardika (Jambura: Jurnal Seni dan Desain, 2020)
This study aims to explore various factors that cause bamboo woven crafts in Tri Rukun Village, Boalemo District, Gorontalo Province, to survive to now. The study used qualitative methods with a case study format. Data were collected through observation, interviews, and literature study. The data were analyzed interactively through the process of data selection and data coding, data categorization, data presentation and discussion, and conclusion. The results showed that the survival of bamboo woven crafts in Tri Rukun Village, Boalemo Regency, Gorontalo Province was caused by various internal and external factors. Internal factors that support it include: 1) there were craft makers who produce it; 2) the availability of raw materials (local bamboo); 3) systematic production methods; 4) the form and function of the product are relevant to the needs. External factors that influence it are: 1) users who use these craft products in their daily lives; 2) support by government institutions;3) support by social and cultural institutions. It was concluded, a craft will survive if supported by various internal and external factors that that have been found. The results of this study can be used to determine the strategy of developing bamboo crafts in Tri Rukun Village and as a guide in researching various factors that cause a type of craft to survive.